Applicability of the DUNDRUM-1 in a forensic Belgium setting. Issue 1 (13th March 2019) - Habets, Petra; Jeandarme, Inge; Kennedy, Harry G.
Abstract : Purpose: Criteria to determine in which level of security forensic patients should receive treatment are currently non-existent in Belgium. Research regarding the assessment of security level is minimal and few instruments are available. The DUNDRUM toolkit is a structured clinical judgement instrument that can be used to provide support when determining security level. The purpose of this paper is to investigate the applicability and validity of the DUNDRUM-1 in Flanders. Design/methodology/approach: The DUNDRUM-1 was scored for 50 male patients admitted at the forensic units in the public psychiatric hospital Rekem. Some files were rated by three researchers who were blind to participants' security status, resulting in 33 double measurements. Findings: Almost all files (96 per cent) contained enough information to score the DUNDRUM-1. Average DUNDRUM-1 final judgement scores were concordant with a medium security profile. No difference was found between the current security levels and the DUNDRUM-1 final judgement scores. Inter-rater reliability was excellent for the DUNDRUM-1 final judgement scores. On item level, all items had excellent to good inter-rater reliability with the exception of one item institutional behaviour which had an average inter-rater reliability. Practical implications: The DUNDRUM-1 can be a useful tool in Flemish forensic settings. It has good psychometric properties. More research is needed to investigate the relationship between DUNDRUM-1 scores and security level decisions by the courts. Originality/value: This is the first study that investigated the applicability of the DUNDRUM-1 in a Belgian setting, also a relative large number of repeated measurements were available to investigate the inter-rater reliability of the DUNDRUM-1.